(untitled) (Global Journals of Research in Engineering, 2013)
The main objective of the present work is to investigate Finite Element Analysis of the forged steel crankshaft In this present research work analysis is conducted on forged Micro Alloy Steel crankshaft This crankshaft is used in new TATA Safari 2 2 L DICOR vehicle which belongs to in line four cylinder crankshaft of four stroke diesel engine But crankshaft is failed for various reasons Therefore there is need for analysis of the crankshaft to find out the reasons of its failure using the FEA analysis In this study a static analysis is conducted on this crankshaft with single crankpin of crankshaft Finite element analysis is performed to obtain the variation of stress magnitude at critical locations With the help of maximum gas pressure at time of combustion total load acting on the crankpin of the crankshaft is calculated In this static analysis of crankshaft loading and boundary condition depend upon the maximum gas pressure acting on the crankpin For the FEA analysis of crankshaft we selected the different element length size for the meshing Meshing is done using the HYPERMESH software with the tetra element shape The static analysis is done analytically This resulted in the load spectrum applied on crankpin area of crankshaft This load is applied to the FE model in ANSYS and boundary conditions were applied according to the engine mounting conditions The analysis is done for maximum loading condition Finally analytical stress calculated value and ANSYS stress value of crankshaft are verified